2000
DOI: 10.2307/3236554
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the understory during 14 years following catastrophic windthrow in two Minnesota forests

Abstract: Abstract. We studied the effects of windthrow on the understory plant species composition of a pine forest (dominated by Pinus strobus) and an oak forest (dominated by Quercus ellipsoidalis). We recorded the presence of vascular plant species in randomly located quadrats in the two forests, and in three microsite types associated with tipup mounds (pit, old soil and new soil) in the pine forest at irregular intervals over the course of 14 years. The understories of the two forests remained distinct throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 46 publications
7
38
2
Order By: Relevance
“…Lasting up to 500 years after formation (Tyrrell and Crow, 1994), tip-up microtopography forms a structural legacy in windthrown forests important to the regeneration of some tree and understory species (Carlton and Bazzaz, 1998;Palmer et al, 2000;Ulanova, 2000). As we expected, salvage logging diminished these legacies of windthrow in our forest.…”
Section: Salvage Logging Effects On Microtopography and Soilmentioning
confidence: 67%
See 3 more Smart Citations
“…Lasting up to 500 years after formation (Tyrrell and Crow, 1994), tip-up microtopography forms a structural legacy in windthrown forests important to the regeneration of some tree and understory species (Carlton and Bazzaz, 1998;Palmer et al, 2000;Ulanova, 2000). As we expected, salvage logging diminished these legacies of windthrow in our forest.…”
Section: Salvage Logging Effects On Microtopography and Soilmentioning
confidence: 67%
“…Yellow birch is known to be a prolific seeder following windthrow (Burns and Honkala, 1990), and its persistence in the region may be linked to severe windthrow events as experienced on the Flambeau in 1977 (Schulte and Mladenoff, 2005). Two legacies of windthrow -downed tree boles and tree tip-ups -are known to provide conditions important to the successful seed germination and establishment of yellow birch as well as other tree and herb species (Beatty, 1984;Carlton and Bazzaz, 1998;Palmer et al, 2000;Ulanova, 2000;Marx and Walters, 2006). Similar to other studies (van Nieuwstadt et al, 2001;Donato et al, 2006), we found no seedlings and few trees and saplings that survived salvage logging (Fig.…”
Section: Overstory Recovery Following Windthrow and Salvage Loggingmentioning
confidence: 99%
See 2 more Smart Citations
“…Facilitation of introductions with time since disturbance could be related to rapid invasion of early successional species (Arnott and Beese, 1997), which are favored by differences in soil texture and chemistry due to less litter incorporation 34 E. A. Gallo et al / Forest Systems (2013) 22 (1), 25-38 into the forest floor (Økland et al, 1999), which derived in lesser organic matter decomposition. Also, presence of newly exposed soil by litter removal generated by skidders or log movement during harvesting, could favor ruderal (defined as species that are first to colonize disturbed lands) introduction, as was observed in tips and mounds that show a high proportion of annual/biennal plants (Palmer et al, 2000). Ruderal species could affect recruitment of N. pumilio regeneration by competitions by niches and resources, which is more problematic in OH than in RH.…”
Section: Discussionmentioning
confidence: 99%